Influence and collaboration in library and information science research: A university perspective - Wattanasiri, Pornnisa; Manorom, Paiboon; Chansanam, Wirapong (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. The objective of this study was to examine the influence and collaboration patterns within library and information science (LIS) research, with a particular focus on the contributions of universities over time. Design/Methodology/Approach. This study used bibliometrics and LIS network analysis to examine 14,517 articles indexed in Scopus from 1954 to 2023. The Bibliometrix R-package was used to identify publication trends, influential institutions, authors, and collaboration networks in the LIS field. Findings. The key findings indicated that Wuhan University was the foremost institution in LIS research, with notable contributions from Chinese scholars who were identified as the most influential authors in the field. The keywords “information science” and “information retrieval” emerged as common thematic areas, reflecting core research interests. The content analysis also revealed that LIS research had robust connections with fields such as physics, computer science, and information technology, underscoring an interdisciplinary trend. Originality/Value. This study offered original insights into the evolving landscape of LIS research, identifying both leadership in academic output and potential gaps in current research coverage. It underscored the necessity for future research to expand the scope of its database and refine keyword selection for more comprehensive representation. The findings contributed to the strategic development of LIS research and the fostering of international collaboration.